Folk religion of the Pennsylvania Dutch: witchcraft, faith healing, and related practices - Orth, Richard L. T. (McFarland & Company, Inc., Publishers, 2018)
"For almost three centuries, the "Pennsylvania Dutch" have practiced white magic, known in their dialect as Braucherei or Powwowing. The art of black magic is known as Hexerei. Healing powers are believed to derive from the Holy Trinity but the powers of Hexerei are from the Devil"--